KESETARAAN GENDER DAN KEDUDUKAN PEREMPUAN DALAM NOVEL ALINA SUHITA - Endang Sumarti; Lukman Hakim (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
In the last decade, there has been an increasing debate about teachings related to women, especially Islam. Many began to question religious teachings that seemed gender biased. In some ways that seem to discredit women. Islam, which normatively teaches the equality of men and women, cannot be separated from the understanding of gender bias. However, the terms and concepts of gender are not widely understood by the public. Stereotypes of women who are presented in society as weak, do not have intelligence, and tend to be passive. In this novel, Allina Suhita describes the character of a pious woman in Alina Suhita. Suhita is a great woman who can put herself into a wife, daughter-in-law, and daughter. The novel teaches us to be strong women and not only that us as women depend on a man. Even in the novel, they still adhere to the old patriarchal teachings, such as the old teachings, women are still considered weak and bringers of disaster. But with the presence of Alina Suhita, she will change all these untrue principles to make women equal to men.